An algebraic characterization of affine manifolds with g-structure satisfying a homogeneity condition (2010)
We give an algebraic characterization of the possible characteristic tensors of an infinitesimally homogeneous affine manifold with $G$-structure. Such concepts were introduced in \cite{PiTausk}.